2022
DOI: 10.1136/bjophthalmol-2021-320644
|View full text |Cite
|
Sign up to set email alerts
|

High myopia as risk factor for the 10-year incidence of open-angle glaucoma in the Beijing Eye Study

Abstract: PurposeTo assess the 10-year incidence of open-angle glaucoma (OAG) and its associations in an adult Chinese population.MethodsLongitudinal observational population-based study. Out of 4439 participants aged 40+ years participating in the Beijing Eye Study in 2001, 2695 individuals (60.7%) were re-examined in 2011, while 397 participants had died (8.5%).ResultsIncident OAG was found in 75 participants among 2494 individuals free of glaucoma at baseline. The 10-year OAG incidence (mean: 3.0%; 95% CI 2.5 to 3.5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 27 publications
0
16
0
2
Order By: Relevance
“…Most of the current literature on the association between myopia and POAG has shown that myopia is a risk factor for POAG across multiple racial and ethnic groups . Notably, a systematic review and meta-analysis on the association between myopia and POAG by Wu et al showed a positive association of risk estimates with an OR of 2.45 (95% CI, 1.80-3.33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the current literature on the association between myopia and POAG has shown that myopia is a risk factor for POAG across multiple racial and ethnic groups . Notably, a systematic review and meta-analysis on the association between myopia and POAG by Wu et al showed a positive association of risk estimates with an OR of 2.45 (95% CI, 1.80-3.33).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the current literature on the association between myopia and POAG has shown that myopia is a risk factor for POAG across multiple racial and ethnic groups. [10][11][12][13][14][23][24][25][26][27][28] Notably, a systematic review and meta-analysis on the association between myopia and POAG by Wu et al 28 showed a positive association of risk estimates with an OR of 2.45 (95% CI, 1.80-3.33). Additionally, a dose-response meta-analysis by Ha et al 23 showed that the association is even stronger between moderate to high myopia and POAG, with a pooled OR of 4.14 (95% CI, 2.57-6.68).…”
Section: Discussionmentioning
confidence: 99%
“… 36 The resulting steepening of the translaminar pressure gradient and pronounced morphological intralaminar changes, with a potential shearing effect on the lamina cribrosa pores, may contribute to the increased prevalence of glaucoma-like and/or glaucomatous optic neuropathy in high myopia. 37 41 In highly myopic eyes, stretching of the lamina cribrosa, together with a flattening of the parapapillary tissue caused by the development of parapapillary gamma zone and delta zone, leads to a flattening of the optic cup, because the spatial difference between the height of the neuroretinal rim and the depth of the optic cup is decreased. 33 , 34 This factor hinders the delineation of the neuroretinal rim from the optic cup and is one of the reasons for increased difficulty in detecting optic nerve damage in a highly myopic ONH.…”
Section: Optic Discmentioning
confidence: 99%
“…High myopia has been identified as a major factor associated with glaucomatous neuropathy, as well as with nonglaucomatous optic nerve damage. 1 , 37 , 40 , 41 , 57 59 An increased prevalence of glaucomatous optic neuropathy may be due to elongation and thinning of the lamina cribrosa, together with associated intralamina tissue changes and steepening of the translamina cribrosa pressure gradient, elongation and thinning of the peripapillary scleral flange as the biomechanical anchor of the lamina cribrosa, and increased distance between the peripapillary arterial circle of Zinn–Haller and the lamina cribrosa. An increased prevalence of nonglaucomatous optic nerve damage in highly myopic eyes may be due to the increased distance from the retinal ganglion cell bodies to the optic disc, leading to a lengthening and potential stretching of the retinal nerve fibers.…”
Section: The Optic Nervementioning
confidence: 99%
“…5,6 Data from the Beijing Eye Study further support this association by suggesting that the 10-year incidence of open-angle glaucoma is 7.3 times higher in eyes with high myopia compared with emmetropic eyes. 7 The dramatic increase in myopia prevalence over time, combined with the global aging of the population, suggests that there will be a corresponding rise in the number of individuals with glaucoma, a leading cause of irreversible vision loss worldwide. As a result, better understanding of the patterns and reasons for the increased risk of glaucoma among people with myopia in different populations, races, and ethnicities is of growing urgency to be able…”
Section: Invited Commentarymentioning
confidence: 99%